Fortalecimiento de la gestión de investigación científica y humanística para la acreditación de las instituciones de educación superior del Caribe colombiano (2017)
The development achieved by higher education institutions in the last decade, has contributed to the continuous improvement of the functions of teaching, research, extension and administrative management to strengthen high quality accreditation processes and their positioning in accordance with the guidelines defined by the National Accreditation System of Colombia (SNA). Based on this, the objective is to determine strategies for strengthening the management of scientific and humanistic research for the accreditation of higher education institutions in the Colombian Caribbean. Through a descriptive investigation, and the application of a quantitative approach, the variables related to the management of research and accreditation of higher education institutions are studied. The population was represented by 39 institutions of the Colombian Caribbean, selecting for the sample the Institute of Technical and Professional Training (INFOTEP) in the Archipelago of San Andrés Providencia and Santa Catalina. The information was collected through the design of a questionnaire, as well as a structured interview and observation. The results were successful after detecting the need to strengthen management, noting that improving management in the accreditation of scientific and humanistic research and by establishing effective strategic guidelines increases the number of enrollees and programs in institutions of higher education. In conclusion, a good management to strengthen the accreditation in scientific and humanistic research raises the quality of the accreditation process of higher education institutions in the Colombian Caribbean. It is recommended to consider the strategic guidelines defined as a possibility whose research contributions allow the generation of new lines of research for the strengthening of management in humanistic scientific research in the context of Colombian higher education institutions.